2018
DOI: 10.1016/j.hpb.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

A modified single-loop reconstruction after pancreaticoduodenectomy reduces severity of postoperative pancreatic fistula in high-risk patients

Abstract: The new mSL reconstruction was safer than conventional SL and faster to perform than DL reconstruction in patients with a high-risk pancreas. It did not influence the rate of POPF, but reduced its severity, leading to less major morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Multivariate analyses are demonstrated in Table . Modified single‐loop reconstruction according to Aghalarov et al had no impact on the occurrence of POPF grade C. Intraoperative blood loss (mean 377 ± 248 mL), intraoperative blood transfusions (24 patients, 3.3%), and mean operative time (366 min) were not identified as risk factors. Mean blood loss was 377 ± 248 mL.…”
Section: Resultsmentioning
confidence: 86%
“…Multivariate analyses are demonstrated in Table . Modified single‐loop reconstruction according to Aghalarov et al had no impact on the occurrence of POPF grade C. Intraoperative blood loss (mean 377 ± 248 mL), intraoperative blood transfusions (24 patients, 3.3%), and mean operative time (366 min) were not identified as risk factors. Mean blood loss was 377 ± 248 mL.…”
Section: Resultsmentioning
confidence: 86%
“…Interestingly, isolated pancreaticojejunostomy decreases the incidence of reoperation in this study. The study conducted by Aghalarov et al and Chhaidar et al showed that isolated pancreaticojejunostomy has less reoperation [10,20]. They showed that the reoperation was largely because of POPF-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 420 duplicate articles were excluded, and we retrieved the remaining 1143 studies based on their titles and abstracts. After excluding irrelevant articles for various reasons, we included a final 14 trials involving a total of 2043 patients [6,[9][10][11][12][19][20][21][22][23][24][25][26][27]. A flowchart of the literature search process is shown in Fig.…”
Section: Study Selection and Trial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 420 duplicate articles were excluded, and we retrieved the remaining 1143 studies based on their titles and abstracts. After excluding irrelevant articles for various reasons, we included a nal 14 trials involving a total of 2043 patients [6,[9][10][11][12][19][20][21][22][23][24][25][26][27]. A owchart of the literature search process is shown in Figure 1, and the characteristics and quality evaluation of the included studies are shown in Table 1.…”
Section: Study Selection and Trial Characteristicsmentioning
confidence: 99%